The Representation of Islam Under Modern Turkey in Orhan Pamuk’s Snow - ALFIAN EKA PURNAMA (LITERA KULTURA : Journal of Literary and Cultural Studies, 2017)
Abstract Representation is a part of literary study that subjectively viewed the cultural context and powerin a society. This is kind of language used by people to say and represent the world meaningfully. In2002, Nobel Prize author “Orhan Pamuk” published his first political-historical novel entitled Snow, thenovel creates a public debate during its publication. The issue of Islam against Secularist appeared inthis novel, which presents the struggle of Headscarf girl and Islam Fundamentalist in Kars City. Thisstudy aims on three different parts to portray the representation of Islam, they are: Representation ofIslam under the Media, Headscarf culture and how Ka as a main character views the tension betweenModern and Traditional city. By focusing on the topic that related to Islam and its problem with SecularState in the novel, this study captured the representation of Islam in different aspect such asrepresentation of Islam under the media, secularist and political Islam. Similarly, headscarf as a part ofreligious dresscode and secular media portray in this study which is achieved by application of Culturaland Representation theory from Stuart Hall and discussed three elements of representation such as:Reflective, Intentional and constructionist. Referring to the findings, the study concludes that therepresentation of Islam under Modern Turkey presents the depiction of Islamic figure, headscarf girl andthe main character perspective about traditional vs modernism. Keywords: Representation, Headscarf, Islam, Secular, Turkey. Abstrak Representasi adalah bagian dari studi sastra yang secara subjektif memandang konteks budayadan kekuasaan dalam suatu masyarakat. Ini adalah jenis bahasa yang digunakan oleh orangorang untukberbicara dan mewakili seluruh dunia dengan penuh makna. Pada tahun 2002, penulis yang menerimaHadiah Nobel "Orhan Pamuk" menerbitkan novel politik-historis pertamanya berjudul Snow, novel inimenciptakan debat dalam masyarakat selama publikasi. Isu Islam melawan sekuler muncul dalam novelini, yang menghadirkan perjuangan gadis berjilbab dan Fundamentalis Islam di Kota Kars. Penelitian inibertujuan pada tiga bagian yang berbeda untuk menggambarkan representasi Islam, yaitu: RepresentasiIslam di bawah Media, budaya jilbab dan bagaimana Ka sebagai karakter utama memandang keteganganantara Kota Kars yang Modern dengan Tradisional. Dengan memusatkan perhatian pada topik yangterkait dengan Islam dan masalahnya dengan Negara Sekuler dalam novel tersebut, penelitian inimenangkap representasi Islam dalam aspek yang berbeda seperti representasi Islam di bawah media,sekuler dan Islam politik. Demikian pula jilbab sebagai bagian dari pakaian religius dan media sekuleryang begitu menonjol membuat penelitian ini menerapkan teori Cultural and Representasi dari StuartHall dan membahas tiga elemen representasi seperti: Reflektif, Disengaja dan Konstruksionis. Mengacupada temuan tersebut, studi tersebut menyimpulkan bahwa representasi Islam di bawah Modern Turkeymenyajikan penggambaran tokoh Islam, gadis jilbab dan perspektif karakter utama tentang tradisional vsmodernisme. Kata Kunci: Representasi, Kerudung, Islam, Sekuler, Turki.